2022
DOI: 10.1002/pros.24462
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of intraductal carcinoma of the prostate in treatment selection for metastatic hormone‐sensitive prostate cancer

Abstract: Background In recent years, the usefulness of androgen receptor axis‐targeted agents (ARATs) such as abiraterone, enzalutamide, and apalutamide for the upfront treatment of metastatic hormone‐sensitive prostate cancer (mHSPC) has been demonstrated. However, it remains unclear which patients would truly benefit from these treatments. Furthermore, intraductal carcinoma of the prostate (IDC‐P) is a known poor prognostic factor in patients with prostate cancer. We investigated the association between the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…This is because the androgen receptor mutation remains the sole clinically relevant mutation in 34% of CRPC patients. Certain androgen receptor mutations may predict responsiveness or resistance to various medicines, but their clinical importance is unknown ( 68 ). Enzalutamide and abiraterone are promising androgen receptor-targeting medicines, but most patients develop resistance to them ( 69 ).…”
Section: Signaling Pathways Involved In Prostate Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…This is because the androgen receptor mutation remains the sole clinically relevant mutation in 34% of CRPC patients. Certain androgen receptor mutations may predict responsiveness or resistance to various medicines, but their clinical importance is unknown ( 68 ). Enzalutamide and abiraterone are promising androgen receptor-targeting medicines, but most patients develop resistance to them ( 69 ).…”
Section: Signaling Pathways Involved In Prostate Cancermentioning
confidence: 99%
“…The PI3K pathway is negatively regulated by the protein Phosphate and Tensin Homologue (PTEN). It has been demonstrated that PTEN loss or inactivation speeds up the development of castration-resistant prostate cancer ( 68 ). Another frequent aberration found in a variety of malignancies is PI3K mutation or amplification, notably of the p110 alpha catalytic subunit ( 71 ).…”
Section: Signaling Pathways Involved In Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the possibility that IDC-P is resistant to ADT, 7,27,37,98 it can be speculated that combined multi-agent therapy and novel treatment options are needed to manage metastatic IDC-P-positive prostate cancer. In a retrospective study of 318 patients with de novo metastatic hormonesensitive prostate cancer, Naito et al 99 found that the survival benefit of adding androgen receptor-pathway inhibitors (ARPIs) to ADT was greater in IDC-P-positive patients than in IDC-P-negative patients.…”
Section: Metastatic Settingmentioning
confidence: 99%
“…Naito et al . [ 4 ] attempted to investigate the association between the presence of intraductal carcinoma of the prostate (IDC-P) and response to androgen receptor axis-targeted agents (ARATs) in metastatic hormone-sensitive prostate cancer (mHSPC).…”
Section: Clinical Utility Of Intraductal Carcinoma Of the Prostate In...mentioning
confidence: 99%